0309 Real-time fine aerosol exposures in taconite mining operations. (21st August 2017) - Huynh, Tran; Ramachandran, Gurumurthy; Quick, Harrison; Raynor, Peter; Alexander, Bruce; Mandel, Jeff
Abstract : Recent studies have shown that taconite workers may be at increased risk for mortality from lung cancer, mesothelioma, and cardiovascular diseases (CVD). The relationship between CVD and occupational dust exposures at these mines has not been well-studied. We conducted an air monitoring campaign to characterise fine aerosol concentrations at 91 locations across six taconite mines using direct-reading instruments to obtain measurements of mass concentrations (PM2.5 or particles with aerodynamic diameter less than 2.5 µm, and respirable particulate matters or RPM), surface area (SA), particle number (PN), and particle size distributions. We fit a Bayesian model with an AR(1) (autoregressive order 1) correlation structure to estimate exposure while accounting for temporal correlation. The highest estimated geometric means (GMs) were observed in the pelletizing and concentrating departments (pelletizing maintenance, balling drum operator, and concentrator operator) for PM2.5 and RPM. SA and PN generally had highest GMs in the pelletizing department that processed powder-like particles into iron pellets. Between-location variability estimates were generally higher than within-location, indicating larger differences in exposure levels at different locations between mines. Ranking between PM2.5 and RPM generally agree with each other, whereas SA and PN were more consistent with each other, with some overlap with PM2.5 and RPM. Differences in ranking these groups may have potential implication for occupational epidemiological studies that rely on exposure information to detect an exposure-response relationship. Future occupational epidemiological studies investigating fine aerosols exposures and health risk are encouraged to consider multiple metrics to see how they influence health outcomes risk.